Resistensi Kekerasan dan Kawin Paksa Terhadap Perempuan dalam Novel Azab Dan Sengsara Karya Merari Siregar - Asia; Ridwan; Ramadani, Aulia Magfira (University of Brawijaya, 2025)
This research explains the existence of complicated social realities related to violence, forced marriage, and resistance to violence in the novel Azab and Sengsara by Merari Siregar. The research method uses descriptive qualitative method to understand a particular phenomenon or situation from an in-depth perspective. The characters in the novel can illustrate how the story is presented with conflicts of domestic violence and forced marriage activities that can damage women's lives. This study aims to analyze the scenes in the novel that show the violence committed by Kasibun against Mariamin and the pressure from Mariamin's mother who wants Mariamin to get married as soon as possible. However, Mariamin eventually showed resistance to violence by reporting her abusive husband to the authorities.